1997
DOI: 10.1128/jcm.35.12.3163-3165.1997
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Shigella sonnei in a clinical microbiology laboratory

Abstract: Laboratory technologists (22%) developed infections with Shigella sonnei. The isolates had the same antibiogram and pulse-field gel electrophoresis pattern as an unknown isolate handled by a laboratory student. Covering faucet handles with paper towels during hand washing in the laboratory was protective. No further cases occurred after the laboratory was cleaned with a phenolic agent and a handle-free faucet was installed.The incidence of infection acquired in hospital microbiology laboratories is approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Mermel et al reported that hands of HCWs became recontaminated from faucet handles during a Shigella outbreak. 183 Soap bars also have the potential to spread contamination from person to person via the hands. 88…”
Section: Efficacy Of Handwashing Using Soap and Watermentioning
confidence: 99%
“…Mermel et al reported that hands of HCWs became recontaminated from faucet handles during a Shigella outbreak. 183 Soap bars also have the potential to spread contamination from person to person via the hands. 88…”
Section: Efficacy Of Handwashing Using Soap and Watermentioning
confidence: 99%
“…The finding of hand operated faucets is not different from several reports from studies conducted in other resource-constraint settings in developing countries [30,35,36]. The use of hand held faucet can predispose to recontamination of the hands from faucet' handles as it was observed during a Shigella sonnei outbreak in a clinical microbiology laboratory [37]. Having a sink without water flowing through the faucet negates the very foundation of hand washing.…”
Section: Discussionmentioning
confidence: 61%
“…However, the use of hand rubs has been found to be very crucial to improvement of compliance with HH in clinical settings. Other aspects where the use of hand rubs may be better than hand washing are: more antimicrobial efficacy, shorter time of procedure, and less potential for recontamination by water or soap particularly in low socioeconomically, resource-constraint settings [37]. The US National Guidelines on Hand Hygiene recommends HH with soap and water as the standard of care and waterless antiseptic hand rubs only in situations where sinks are not available [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…13 The need for close supervision of trainees was underscored in the report of an outbreak of shigella infection in a hospital laboratory where a medical technology student worked with the organism. 14 Only 15% of students reported vaccination against tuberculosis. As most persons receive BCG at birth, respondents may not be aware of their immunisation status.…”
Section: Discussionmentioning
confidence: 99%